Evaluation of the use of oseltamivir prophylaxis in the control of influenza outbreaks in long-term care facilities in Alberta, Canada: a retrospective provincial database analysis. Issue 7 (5th July 2016) - Ye, Ming; Jacobs, Angela; Khan, Muhammad Naeem; Jaipaul, Joy; Oda, Joanna; Johnson, Marcia; Doroshenko, Alexander
Abstract : Objectives: To evaluate the impact of oseltamivir prophylaxis in the management and control of influenza outbreaks in long-term care facilities in Alberta, Canada. Setting and participants: Long-term care facilities where 127 influenza outbreaks were reported to public health authorities in Alberta, Canada, during two influenza seasons from 2013 to 2015. Design and outcome measures: Using routinely collected surveillance and administrative data, we examined the association between decision-making time for oseltamivir recommendation as prophylaxis strategy for influenza outbreaks in long-term care facilities (explanatory variable) and the duration of an influenza outbreak, the postprophylaxis risk of influenza-like illness and hospitalisation among residents of long-term care facilities in Alberta (outcome variables) using multivariable linear and Poisson regression models. Results: Oseltamivir prophylaxis decision-making time was positively associated with the postintervention duration of an outbreak, with a 1-day delay in making decision on oseltamivir prophylaxis associated with 2.22 (95% CI 1.37 to 3.06) more days of the duration of an outbreak after controlling for potential confounding effect of the number of residents at risk at intervention, outbreak progression time, prevalence of influenza-like illness during outbreak progression, facility location, presence of mixed strain and based on optimal timing of oseltamivir prophylaxis. Although not statistically significant, a 1-day delay in making decision on oseltamivir prophylaxis was associated with a 5% (95% CI −1% to 11%) increase in the postintervention risk of influenza-like illness, and a 6% (95% CI −8% to 22%) increase in the postintervention risk of hospitalisation after controlling for the same potential confounders. Conclusions: Our study demonstrated benefits of using oseltamivir prophylaxis to shorten the duration of influenza outbreaks; however, there were no significant differences in the influenza-like illness and hospitalisation risk occurring after the intervention. Surveillance data may offer means of rapid evaluation of oseltamivir prophylaxis in long-term care facilities as a public health measure.